Structural and Kinetic Characterization of an Archaeal β-Class Carbonic Anhydrase - Smith, Kerry S. (American Society for Microbiology, 2000)
The β-class carbonic anhydrase from the archaeon Methanobacterium thermoautotrophicum (Cab) was structurally and kinetically characterized. Analytical ultracentrifugation experiments show that Cab is a tetramer. Circular dichroism studies of Cab and the Spinacia oleracea (spinach) β-class carbonic anhydrase indicate that the secondary structure of the β-class enzymes is predominantly α-helical, unlike that of the α- or γ-class enzymes. Extended X-ray absorption fine structure results indicate the active zinc site of Cab is coordinated by two sulfur and two O/N ligands, with the possibility that one of the O/N ligands is derived from histidine and the other from water. Both the steady-state parameters k(cat) and k(cat)/K(m) for CO(2) hydration are pH dependent. The steady-state parameter k(cat) is buffer-dependent in a saturable manner at both pH 8.5 and 6.5, and the analysis suggested a ping-pong mechanism in which buffer is the second substrate. At saturating buffer conditions and pH 8.5, k(cat) is 2.1-fold higher in H(2)O than in D(2)O, consistent with an intramolecular proton transfer step being rate contributing. The steady-state parameter k(cat)/K(m) is not dependent on buffer, and no solvent hydrogen isotope effect was observed. The results suggest a zinc hydroxide mechanism for Cab. The overall results indicate that prokaryotic β-class carbonic anhydrases have fundamental characteristics similar to the eukaryotic β-class enzymes and firmly establish that the α-, β-, and γ-classes are convergently evolved enzymes that, although structurally distinct, are functionally equivalent.